2007
DOI: 10.1136/gut.2006.105122
|View full text |Cite
|
Sign up to set email alerts
|

 -Opioid receptor activation prevents acute hepatic inflammation and cell death

Abstract: Background and aims: The detrimental impact of opioid agonist on the clinical management of inflammatory diseases remains elusive. Given the anti-inflammatory properties of the m-opioid receptor (MOR) agonists at the intestinal barrier, we hypothesised that MOR activation might also dampen acute hepatic inflammation and cell death-major determinants in the pathogenesis of liver diseases. Patients and methods: The expression of MOR in liver biopsy specimens and peripheral blood mononuclear cells of untreated pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 55 publications
1
24
1
Order By: Relevance
“…This concept is further supported by the suppression of the inhibitory effect of DAMGO on MPO and NF-kB in acute colitis with a Bcl family inhibitor. These findings are in line with the reported antiapoptotic properties of μORs in hepatocytes as a mechanism underlying the protective effect of μOR agonists in acute hepatitis in mouse [23]. Bcl-xL is a zinc finger protein of the bcl family involved in cell death regulation, which binds with and sequesters proapoptotic effectors, such as Bax, Raf-1 kinase or other factors, forming heterodimers that promote cell survival and protect tissue from injury-induced cell death [27, 28].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This concept is further supported by the suppression of the inhibitory effect of DAMGO on MPO and NF-kB in acute colitis with a Bcl family inhibitor. These findings are in line with the reported antiapoptotic properties of μORs in hepatocytes as a mechanism underlying the protective effect of μOR agonists in acute hepatitis in mouse [23]. Bcl-xL is a zinc finger protein of the bcl family involved in cell death regulation, which binds with and sequesters proapoptotic effectors, such as Bax, Raf-1 kinase or other factors, forming heterodimers that promote cell survival and protect tissue from injury-induced cell death [27, 28].…”
Section: Discussionsupporting
confidence: 89%
“…Upregulation of μOR mRNA has been reported in different animal models of intestinal inflammation [20, 21] and in patients with inflammatory bowel disease (IBD) [22], whereas μOR mRNA expression was impaired in chronic hepatitis [23]. Furthermore, activation of μORs with selective agonists has been shown to protect from intestinal inflammation induced by ischemia/reperfusion[24], prevent acute hepatitis [23] and ameliorate acute experimental colitis induced by intrarectal 2,4,6-trinitrobenzebesulfonic acid (TNBS) [20]. …”
mentioning
confidence: 99%
“…This TH2-prone phenotype in T-OpR mice may appear in contrast with previous literature showing that acute and chronic morphine administration (Lockwood et al 1996;Sacerdote et al 1997Sacerdote et al , 2000West et al 1997;Roy et al 2001bRoy et al , 2004Saurer et al 2004), mu opioid peptide injection (Chakass et al 2007), and heroin addiction (Azarang et al 2007) resulted in a Th2 biased immune response. In contrast also, acute or chronic treatment with the general opioid antagonist naltrexone decreased TH2 and/or augmented TH1 responses (Sacerdote et al , 2000(Sacerdote et al , 2003Jazani et al 2010;Kelschenbach et al 2005), while chronic naloxone-methiodide augmented both IFNγ and IL-4 in mouse colon (Philippe et al 2003).…”
Section: Discussioncontrasting
confidence: 61%
“…The findings about the triggering or inhibitory effects of opiates on inflammation systems are now conflicting. Although some studies emphasized anti-inflammatory effects of some opiates such as morphine [20], some others showed that the dual effect of opium on inflammation might be dependant to the type of the opioid receptors in the especial organs [21], that µ opioid receptor activation prevents acute hepatic inflammation and cell death and activation of the δ-opioid receptor inhibits serum deprivation induced apoptosis of human liver cells via the activation of PKC (protein kinase C) and the mitochondrial pathway [22,23], while some studies showed that administration of opioid receptors antagonists attenuate liver fibrosis [24]. Thus, impact of opium on liver inflammation systems should be assessed considering the types of activated opiate receptors in liver tissue.…”
Section: Discussionmentioning
confidence: 99%